UAE Industrial Heritage: A Study of the Traditional Ship Industry Site in Dubai as One of the Industrial Heritage Sites in the U.A.E: (Jaddaf Site) in Dubai as a Case Study - Al-Mazimmi, Samirah; Jamhawi, Monther; Sukkar, Ahmad (Al-Adab Journal, 2024)
There were various industries and crafts directly related to the sea, the most important of which was the manufacture of wooden ships that children inherited from their ancestors. Unfortunately, with the industrial boom and the advent of oil, this craft and industry ceased to exist and only remained in the Emirate of Dubai. Furthermore, no industrial heritage site has been nominated from the Arab countries so far. This article focuses on the traditional shipbuilding profession, called Qalafa, in Dubai as a type of industrial heritage. It also highlights sites that are neither well protected nor studied. The preservation of industrial heritage in the Emirate is weak due to insufficient awareness, documentation, and protection. Therefore, this study addressed international conventions that call for preserving and protecting industrial heritage sites, facilities, and scenes. One of the results of this article is supporting the revival of the profession through the adaptive use of industrial buildings, the display of handicrafts in museums, the establishment of annual festivals such as sailing boat races, and the increase in the interest of government either through establishing associations that adopt such industries or through organizing workshops for manufacturing of traditional ships.